2020
DOI: 10.1002/ehf2.13083
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to SARS‐CoV‐2 infection in patients with reduced left ventricular ejection fraction

Abstract: Aims Cardiovascular disease has been recognized as a major determinant of coronavirus disease 2019 (COVID‐19) vulnerability and severity. Angiotensin‐converting enzyme (ACE) 2 is a functional receptor for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and is up‐regulated in patients with heart failure. We sought to examine the potential association between reduced left ventricular ejection fraction (LVEF) and the susceptibility to SARS‐CoV‐2 infection. Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…More recently, Matsushita et al used a single-center registry of patients with a history of acute coronary syndrome to examine the correlation between baseline LVEF and the combined endpoint of COVID-related hospitalization or death. ( 20 ) Only a small minority (4%) of these patients underwent a COVID diagnostic test. Although a higher proportion of patients with low LVEF met the combined endpoint than among those with preserved LVEF, the study was limited: the incidence of COVID testing was much higher among low-LVEF patients, there were only 18 total events, and the endpoint was driven entirely by hospitalization, not death.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Matsushita et al used a single-center registry of patients with a history of acute coronary syndrome to examine the correlation between baseline LVEF and the combined endpoint of COVID-related hospitalization or death. ( 20 ) Only a small minority (4%) of these patients underwent a COVID diagnostic test. Although a higher proportion of patients with low LVEF met the combined endpoint than among those with preserved LVEF, the study was limited: the incidence of COVID testing was much higher among low-LVEF patients, there were only 18 total events, and the endpoint was driven entirely by hospitalization, not death.…”
Section: Discussionmentioning
confidence: 99%
“…One small study found a higher likelihood of intubation or death in COVID-19 patients with LVEF < 55% compared to those with LVEF ≥ 55%, but this study did not differentiate between patients with a normal EF and those with a hyperdynamic EF [9] . Similarly, another study found that patients with LVEF < 40% had a significantly higher incidence of COVID-19 related hospitalization or death than LVEF ≥ 40% [10] .…”
Section: Introductionmentioning
confidence: 82%
“…The question arises, whether pre-existing cardiac damage is relevant to the consequences of COVID-19 disease. In a large retrospective cohort study including 1162 patients with acute coronary syndrome (ACS), reduced LVEF was associated with increased susceptibility to COVID-19 [62]. However, in a multicenter cohort study with 305 COVID-19 patients, cardiac structural abnormalities were detected in nearly two-thirds of the patients receiving transthoracic echocardiography-contributing to a higher mortality rate [63].…”
Section: The Role Of Sars-cov-2 Related Cardiac Injury In Covid-19 Patients With Aismentioning
confidence: 99%